Vaginal wind: A literature review. (July 2017) - Neels, Hedwig; Mortiers, Xavier; de Graaf, Sybrich; Tjalma, Wiebren A.A.; De Wachter, Stefan; Vermandel, Alexandra
Abstract: Objective: In the medical literature, there is little known about vaginal wind, though from clinical expertise, it turns out to be a consistent and underreported problem. The aim of this review was to collect the available literature about the different aspects of vaginal wind. Study design: A systematic literature search was conducted using three databases until December 2015. The search strategy was built using relevant synonyms of vaginal wind. Study characteristics were extracted. Risk of bias, the quality of the relevant studies and the level of evidence was judged. Results: Eleven studies met the inclusion criteria. Vaginal wind occurs on random movements and during or after coitus. The prevalence ranges from one to 69%. The pathophysiology is unclear and the incidence unknown. Known risk factors are vaginal delivery and urinary incontinence. Provoking factors are coitus, digital stimulation, cunnilingus and exercising. Female sexual function is decreased. The sexual function of male partners with vaginal wind is not influenced. Overall vaginal wind leads to a decrease in the quality of live and can have cause social isolation. The treatment is related to the cause and mainly not successful. Tampons can be used for treatment as well as prevention. Conclusion: Vaginal wind is an underestimated health issue with a severe impact on sexual functioning. Adequate research is needed regarding the influence of sexual activity, weight, age, parity, the underlying pathophysiological mechanisms, prevention and treatment.